2008
DOI: 10.1242/jeb.015248
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of putative oxygen-sensing cells in the fish gill

Abstract: SUMMARYWe investigated the distribution of serotonin (5-HT)-containing neuroepithelial cells (NECs), the putative O 2 sensing cells, in the gills of four species of fish: trout (Oncorhynchus mykiss), goldfish (Carassius auratus), trairão (Hoplias lacerdae) and traira (Hoplias malabaricus) using immunohistochemical markers for 5-HT, synaptic vesicles and neural innervation. We found that all fish had a cluster of innervated, serotonergic NECs at the filament tips, but there were species-specific distributions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 46 publications
6
42
0
Order By: Relevance
“…6A,C). These cells were similar in morphology and location to those previously described in the filaments of all other species of fish studied (Coolidge et al, 2008;Jonz et al, 2004;Regan et al, 2011;Saltys et al, 2006;Tzaneva and Perry, 2010). Additionally, Type I cells, just as in NECs in this same location in goldfish (Carassius auratus) and trout (O. mykiss), did not label with the HNK-1 antibody, suggesting they are either not derived from the neural crest, or more probably, not proliferative (Porteus et al, 2013), as some neural crest cells stop expressing HNK-1 once they differentiate (Metcalfe et al, 1990).…”
Section: Type I Cellssupporting
confidence: 83%
See 4 more Smart Citations
“…6A,C). These cells were similar in morphology and location to those previously described in the filaments of all other species of fish studied (Coolidge et al, 2008;Jonz et al, 2004;Regan et al, 2011;Saltys et al, 2006;Tzaneva and Perry, 2010). Additionally, Type I cells, just as in NECs in this same location in goldfish (Carassius auratus) and trout (O. mykiss), did not label with the HNK-1 antibody, suggesting they are either not derived from the neural crest, or more probably, not proliferative (Porteus et al, 2013), as some neural crest cells stop expressing HNK-1 once they differentiate (Metcalfe et al, 1990).…”
Section: Type I Cellssupporting
confidence: 83%
“…This was surprising because previous studies have shown that the reflex hypoxic bradycardia exhibited by this species is mediated exclusively by externally oriented receptors (McKenzie et al, 1991a;McKenzie et al, 1991b). It should be noted, however, that our study only examined the first gill arch and that elimination of the hypoxic bradycardia required denervation of all four gill arches, and NECs have been found in all four gill arches of all species studied to date (Coolidge et al, 2008;Jonz and Nurse, 2003;Zhang et al, 2011). Thus, it is possible that chemoreceptors exclusively oriented to sample water could be located on other gill arches of bowfin.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations